2022
DOI: 10.3390/ijms232112821
|View full text |Cite
|
Sign up to set email alerts
|

Three Heat Shock Protein Genes and Antioxidant Enzymes Protect Pardosa pseudoannulata (Araneae: Lycosidae) from High Temperature Stress

Abstract: Pardosa pseudoannulata (P. pseudoannulata) is an essential natural predatory enemy in rice ecosystems. The fluctuating climate may cause them to experience heat stress, whereas heat shock proteins (HSPs) and antioxidant enzymes help resist heat damage. Herein, we cloned and characterized the full-length genes PpHSP27, PpHSP60, and PpHSC70 from P. pseudoannulata. Changes in gene expression levels and superoxide dismutase (SOD), catalase (CAT), and glutathione transferase (GST) activities in adult male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…With the increase in environmental temperature, the genetic diversity of P. pseudoannulata populations show a decreasing trend (Sun et al 2007). The expression levels of six heat‐shock protein genes in P. pseudoannulata are significantly upregulated under high‐temperature stress, compared with 25°C (Fu et al 2022; Sun et al 2021). Currently, some gene studies related to temperature stress in spiders have been published, but there is no research specifically focused on the miRNAs of spiders.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in environmental temperature, the genetic diversity of P. pseudoannulata populations show a decreasing trend (Sun et al 2007). The expression levels of six heat‐shock protein genes in P. pseudoannulata are significantly upregulated under high‐temperature stress, compared with 25°C (Fu et al 2022; Sun et al 2021). Currently, some gene studies related to temperature stress in spiders have been published, but there is no research specifically focused on the miRNAs of spiders.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the current context of global warming, such research can provide important theoretical foundations for studying biological responses to high-temperature stress. Current research on spiders' response to high temperatures mainly concentrates on the expression of heat shock protein genes (Sun et al 2021) and the function of heat shock protein genes (Fu et al 2022). There is comparatively less research on the relationship between microRNAs (miRNAs) and temperature in P. pseudoannulata.…”
Section: Introductionmentioning
confidence: 99%
“…2021) and the function of heat shock protein genes (Fu et al . 2022). There is comparatively less research on the relationship between microRNAs (miRNAs) and temperature in P. pseudoannulata .…”
Section: Introductionmentioning
confidence: 99%
“…The wolf spider Pardosa pseudoannulata (Araneae: Lycosidae), which is a hunting spider, 30 mainly feeds on rice pests such as planthoppers, leafhoppers, and other Lepidoptera insects. [31][32][33] It has strong adaptability to the environment and is widely distributed, [34][35][36][37][38] generally being found in wet habitats near the edge of water bodies. 39 Research has shown that the vitellogenin receptor gene 38 and the functional ecdysteroid Ponasterone A (PA) 40 are vital to the growth and development of Pardosa pseudoannulata.…”
Section: Introductionmentioning
confidence: 99%